Designing a New Framework for the Patient Affected with Heart Problem - Hwang, I-Shyan; Beybutyan, D. (Mathematical Problems of Computer Science, 2021)
According to recent research healthcare is becoming more expensive and less accessible for general public. Cellular phones and GSM networks are considered as cheapest and most accessible means of communications, so they can be used as one of the best devices in creating healthcare systems. During recent years several commercial tools are introduced to monitor and improve health. Each of the present pieces of software in the field of heart diseases accounts for a separate task. In present work we try to define a new frame work and software that can cover all kinds of heart disorders is an ideal for patients and that they can use it with the least know-how and effort. We designed the software so, that it should be easy to use, independent from any operating system and hardware of cell phone, independent from place as well as it can predict heart attack and in case of emergency, immediately send the alarm.